Influence of Ionizing Radiation on the Allergic Reactivity of Tuberculosis-Infected Laboratory Animals - Kassich, Volodymyr; Кассіч, Володимир Юрійович; Kasianenko, Oksana; Касяненко, Оксана Іванівна; Zazharskiy Vladymyr, Vladymyr; Zazharskiy, Volodymyr; Zazharskyi, Vladymyr; Zazharskyi, Volodymyr; Zazharskiy, V.; Zazharskyi, V.; Zazharskiy, Volodymyr V.; Zazharskiy, V. V.; et al. (Поліський нац. ун-т, 2021)
Allergic examination using PPD-tuberculins is the main method of life-time tuberculosis diagnostics in farm animals and poultry. However, it is known about a decrease in the diagnostic value of allergic reactions after irradiation of animals, the occurrence of non-specific, pseudo-allergic reactions. One of the reasons for the manifestation of non-specific reactions may be autosensitisation (autoallergisation) of the body by the breakdown products of personal tissues, which is especially pronounced with radiation damage. Ionizing radiation affects the manifestation of tuberculin sensitivity, the course of tuberculosis and autoimmune processes in the body. Differential diagnostics of non-specific tuberculin reactions remains not yet a fully solved problem, although there are many tests for its implementation. After the accident at the Chernobyl nuclear power plant, a considerable number of animals remained in the adjacent territories contaminated with radioactive substances, including those infected with the causative agent of tuberculosis and atypical mycobacteria. It is known that irradiation leads to autosensitisation of the body by the breakdown products of its own tissues and the development of non-specific pseudoallergic reactions to heterologous allergens. Therefore, work was carried out to study the allergic reactivity of tuberculosis patients and laboratory animals sensitised with atypical mycobacteria irradiated with gamma radiation (200 guinea pigs). It was established that 14-60 days after infection with tuberculosis pathogens, 90-100% of cavies developed allergic reactions to PPD-tuberculin for mammals and poultry, mainly to a homologous allergen. Allergic reactivity persisted until 90 days of the study. After exposure to sublethal (non-lethal) doses of gamma rays, infected and intact cavies developed non-specific reactions to tuberculin and heterologous allergens: mallein and brucellin. In cavies uninfected with the causative agent of tuberculosis, 7 days after gamma radiation exposure, non-specific reactions to mycobacterial allergens were observed at a dose load of 200 R in 16.6%; 150 R – 5.3% in the group, and after 27 days in irradiated doses of 50 R and 100 R in 25% and 33% of the studied animals, respectively. Isolated reactions to brucellin and mallein occurred in animals infected with the causative agent of tuberculosis and intact animals 60 days after irradiation with doses of 50 R, 100 R and 150 R. The manifestation of non-specific allergies in irradiated animals depended on the radiation dose rate and radiosensitivity of the animals. Алергічне дослідження з використанням ППД-туберкулінів є основним методом прижиттєвої діагностики туберкульозу сільськогосподарських тварин та птиці. Проте відомо про зниження діагностичної цінності алергічних реакцій після опромінення тварин, появу неспецифічних, псевдоалергічних реакцій. Однією з причин прояву неспецифічних реакцій може бути аутосенсибілізація (аутоалергізація) організму продуктами розпаду особистих тканин, що особливо виражено за променевого ураження. Іонізуюча радіація впливає на прояв туберкулінової чутливості, перебіг туберкульозу та аутоімунні процеси в організмі. Диференціальна діагностика неспецифічних туберкулінових реакцій лишається поки що не повністю вирішеною проблемою, хоча існує цілий ряд тестів для її здійснення. Після аварії на Чорнобильській АЕС на прилеглих забруднених радіоактивними речовинами територіях лишилося значне поголів’я тварин, у тому числі інфікованих збудником туберкульозу та атиповими мікобактеріями. Відомо, що радіаційне опромінення призводить до аутосенсибілізації організму продуктами розпаду власних тканин і розвитку неспецифічних псевдоалергічних реакцій на гетерологічні алергени. Тому була проведена робота з вивчення алергічної реактивності хворих на туберкульоз і сенсибілізованих атиповими мікобактеріями опромінених гамма-радіацією лабораторних тварин (200 морських свинок). Було встановлено, що через 14–60 діб після зараженням збудниками туберкульозу у 90–100 % мурчаків розвивались алергічні реакції на ППД-туберкулін для ссавців та птиці, переважно на гомологічний алерген. Алергічна реактивність зберігалась до 90 доби дослідження. Після опромінення сублетальними (не летальними) дозами гамма-променів у заражених та інтактних морських свинок розвивались неспецифічні реакції на туберкулін і гетерологічні алергени: малеїн та бруцелін. У незаражених збудником туберкульозу мурчаків через 7 діб після опромінення гамма-випромінюванням спостерігали неспецифічні реакції на мікобактеріальні алергени при дозовому навантаженні 200 Р у 16,6 %; 150 Р – 5,3 % по групі, а через 27 діб у опромінених дозами 50 Р та 100 Р у 25 % та 33 % досліджених тварин, відповідно. У інфікованих збудником туберкульозу та інтактних тварин через 60 діб після опромінення в дозах 50 Р, 100 Р та 150 Р виникали поодинокі реакції на бруцелін та малеїн. Прояв неспецифічної алергії у опромінених тварин залежала від потужності дози опромінення та радіочутливості тварин.
Вплив іонізуючої радіації на стан алергічної реактивності інфікованих туберкульозом лабораторних тварин
Зажарський Володимир Володимирович https://orcid.org/0000-0003-2674-2494
Keywords: allergic studies; алергічні дослідження; tuberculin; туберкулін; heterologous allergens; гетерологічні алергени; gamma radiation; гамма-опромінення; mycobacteria; мікобактерії